Aloe Vera coated Dextran Sulfate/Chitosan nanoparticles (Aloe Vera @ DS/CS) encapsulating Eucalyptus essential oil with antibacterial potent property. Issue 6 (13th April 2023) - Darwish, Mirhane Mostafa; Elneklawi, Mona S.; Mohamad, Ebtesam A.
Abstract: The goal of this work is to encapsulate Eucalyptus staigeriana essential oil in biopolymer matrices, to optimize the biological effects and the antibacterial properties of this oil. In this study, Eucalyptus extract was encapsulated in Aloe Vera coated Dextran Sulfate/Chitosan nanoparticles to form a hydrogel with potent properties. In this study, Eucalyptus extract was loaded on to Aloe Vera coated Dextran Sulphate/Chitosan nanoparticles to obtain a nano-hydrogel with potent properties. The characterization of nanoparticles was evaluated using transmission and scanning electron microscopes, dynamic light scattering, Fourier transform infrared spectroscopy, differential scanning calorimetry and antibacterial activity. The E. staigeriana release profile from the prepared nanoparticles was studied in vitro at a pH of 7.4. The results showed that this nano-carrier controls Eucalyptus release. Aloe Vera coated Dextran Sulfate/Chitosan nanoparticles encapsulated with E. staigeriana inhibited the bacteria by 47.27%. These investigations concluded that E. staigeriana loaded Aloe Vera coated Dextran Sulfate/Chitosan hydrogel could be used as a powerful dressing material to accelerate wound healing.